а) 4x² - 4x - 15 < 0
D = b² - 4ac = 16 + 4*4*15 = 16 + 240 = 256
x₁ = (-b + √D) / 2a = (4 + 16) / 8 = 20 / 8 = 2,5
x₂ = (-b - √D) / 2a = (4 - 16) / 8 = -12 / 8 = -1,5
(x - 2,5)(х + 1,5) < 0
{ x < 2,5
{ x < -1,5
ответ: (-1,5; 2,5)
б) x² - 81 > 0
(x - 9)(x + 9) > 0
{ x > -9
{ x > 9
ответ: (-9; 9)
в) x² < 1,7х
x² - 1,7х < 0
х(x - 1,7) < 0
{ x < 0
{ x < 1,7
ответ: (0; 1,7)
г) x( x + 3) - 6 < 3 (x + 1)
x² + 3x - 6 - 3x - 3 < 0
x² - 9 < 0
(x - 3)(x + 3) < 0
{ x < -3
{ x < 3
ответ: (-3; 3)
№ 1.
1)5а + 5b = 5(a + b)
2)7a - 7b = 7(a - b)
3)2.5x - 2.5y = 2.5(x - y)
4)1/3x + 1/3y = 1/3(x + y)
№ 2
1)16x - 8 = 8(2x - 1)
2)24a + 6 = 6(4a + 1)
3)18b + 9 = 9(2b + 1)
4)25c - 5 = 5(5c - 1)
5)16c - 24d = 8(2c - 3d)
6)21m + 28n = 7(3m + 4n)
№ 3
1)ab + a = a(b + 1)
2)mn - m = m(n - 1)
3)a^3b - b = b(a^3 - 1)
4)x^3y + y = y(x^3 + 1)
5)a^3b^3 - b = b(a^3b^2 - 1)
6)x^3y^2 + y = y(x^3y + 1)
7)a^3b^2 + b^2 = b^2(a^3 + 1)
8)x^3y^2 - y^2 = y^2(x^3 - 1)
9)a^3b^2 - ab^2 = ab^2(a^2 - 1)
10)x^3y^2 + xy^2 = xy^2(x^2 + 1)
№ 4
1)2ab - 4a = 2a(b - 2)
2)3xy + 6x = 3x(y + 2)
3)5mn^2 + 10m = 5m(n^2 + 2)
4)3x^2y - 15x^2 = 3x^2(y - 5)
5)27y^4 - 18y^2 = 9y^2(3y^2 - 2)
6)42p^3 + 14p^2 = 14p^2(3p + 1)
x²-3x≤0
x(x-3)≤0
x=0 или x-3=0
x=3
ответ от 0 включительно до 3 включительнл